2002
DOI: 10.1097/00008469-200206000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate and aspirin in combination have an enhanced effect on apoptosis in human colorectal cancer cells

Abstract: Laboratory and epidemiological studies suggest that butyrate, a metabolic product of microbial fermentation of dietary fibre, and aspirin, a non-steroidal antiphlogistic drug, both reduce the risk of developing colon cancer. Notably, few data exist on potential interactions of these two substances. In this study, the effects of a butyrate-aspirin combination on human colon cancer cells were compared with treatment with aspirin or butyrate alone. Both substances decreased proliferation and induced differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For dietary fibre, binding and dilution of bile salts, inhibition of protein kinase-C activity and the activity of butyrate that is produced in large bowel by fermentation, have all been proposed as possible mechanisms [1]. Butyrate may promote cellular apoptosis, alter the expression of p53 oncogene and in a recent study in human cancer colonocytes it was shown to have synergistic protective effect with aspirin [6]. These agents can moderate prostaglandin synthesis, as they are primarily cyclooxygenase (COX) inhibitors, an enzyme which converts arachidonate to prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…For dietary fibre, binding and dilution of bile salts, inhibition of protein kinase-C activity and the activity of butyrate that is produced in large bowel by fermentation, have all been proposed as possible mechanisms [1]. Butyrate may promote cellular apoptosis, alter the expression of p53 oncogene and in a recent study in human cancer colonocytes it was shown to have synergistic protective effect with aspirin [6]. These agents can moderate prostaglandin synthesis, as they are primarily cyclooxygenase (COX) inhibitors, an enzyme which converts arachidonate to prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…40 On the other hand, degradation of mutant p53 protein induced by vorinostat is in agreement with data from two other reports also showing depletion of mut-p53 by HDAC-Is. 41,42 In addition, it was demonstrated that a novel gain of function conferred by certain p53 mutants was linked to fluoropyrimidine chemoresistance, 34,43 and several clinical studies have revealed higher resistance to fluoropyrimidine therapy of tumors expressing p53 mutants. 33 More prominently, it was recently reported, in colon cancer cells transfected with mut-p53, an increased TS mRNA and protein expression as well as activity, associated with decreased sensitivity to 5-FU and antifolates, compared to the wild-type parental cells.…”
Section: Methodsmentioning
confidence: 99%
“…Considering celecoxib, the mechanisms by which NSAID and selective COX-2 inhibitors are acting are now relatively well characterised [2,42,51]. In vitro, it was shown that butyrate may directly increase COX-2 expression (52), and that aspirin or NS-398, another COX-2 selective inhibitor, can exert synergistic anti-proliferative and pro-apoptotic effects [52,53]. However, by using six different colon carcinoma cell lines expressing different levels of COX-2, we found no synergistic effects of celecoxib and butyrate on cell proliferation and apoptosis (unpublished data).…”
Section: Discussionmentioning
confidence: 99%